Optimizing and Evaluation of Scour Depth Prediction Techniques for Columns as a Component of Complex Bridge Piers - Ata Amini; Thamer Mahmmod; Abdul Ghazali (Advances in Civil Engineering and Environmental Science, 2024)
This study investigates the scour depths at isolated columns, integral components of complex piers, through a series of experiments conducted in a 46 m rectangular flume designed for clear-water scour testing. A total of 34 tests were performed, examining isolated columns, including piles and pile caps, at various elevations above an undisturbed streambed, while maintaining a consistent flow depth of 0.24 m and using sediment with an average particle size of 0.8 mm. Normalization of the collected data led to the development of empirical equations to estimate scour depths, focusing on the relationship between normalized scour depth and column location. The results revealed significant discrepancies between estimated and measured scour depths. While the Federal Highway Administration's HEC-18 method demonstrated a marginally better prediction for isolated columns than the Florida Department of Transportation (FDOT) method, both approaches exhibited considerable inaccuracies. This investigation emphasizes the need for a more comprehensive understanding of scour behavior in individual column components to enhance the accuracy of the superposition method for predicting scour in complex pier configurations.